2019
DOI: 10.3126/njms.v4i1.24119
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Study of Proximal end of Femur of Nepalese People

Abstract: Introduction: The femur is the largest and strongest bone of the body that forms the skeleton of the thigh. The morphometry of proximal end of femur are variable between different individuals with different Nationality. The aims and objective of the study is to find out the morphometric measurements- Femur Length, Femur head diameter, Femur neck shaft angle, and Femur neck length, breadth and thickness. Methods: A total of 75 femurs of both sex were collected from the Department of Anatomy, MCOMS, Pokhar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In a Hong Kong study, males had a mean femoral length of 45.1 cm, and females had 43.7 cm (Hoaglund & Low, 1980), both exceeding Sri Lankan values(Right-42.8(SD±2.64), ). Conversely, a study in Nepal reported a lower mean length of 42.0 ± 2.81 cm, indicating regional variations in body proportions (Mukhia et al, 2019).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In a Hong Kong study, males had a mean femoral length of 45.1 cm, and females had 43.7 cm (Hoaglund & Low, 1980), both exceeding Sri Lankan values(Right-42.8(SD±2.64), ). Conversely, a study in Nepal reported a lower mean length of 42.0 ± 2.81 cm, indicating regional variations in body proportions (Mukhia et al, 2019).…”
Section: Discussionmentioning
confidence: 86%
“…The Nepalese study found angles of 122º±7.71 and 131.3º±5.17 for right and left femurs (Mukhia et al, 2019), while a Pakistani study recorded 130.3º±6.1 (Umer et al, 2010). These figures differed from our study , Left-127.59(SD±2.06)) , even within the same Asian population, highlighting potential limb-specific differences.…”
Section: Discussionmentioning
confidence: 98%
“…It was 13.10±0.88 cm for right femurs and 13±0.92 cm for left femurs. 7 A similar cadaveric study from India reported mean diameter of femoral head to be 4.19±0.19 cm. 12 In a cross-sectional study, Riad et al aimed to measure the femoral head diameter radiologically and to find out male-female variation and relationship with the stature in Bangladeshi population.…”
Section: Discussionmentioning
confidence: 90%
“…Mukhia and colleagues assessed the morphometric parameters of 75 adult cadaveric femurs. 7 However, the age group of the sample ranged from 30 to 60 years. Hip arthroplasties usually happen in people aged 50 years or more.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies evaluated the morphometry of the proximal femur in Nepal. 11,12 Hence, the primary objective of this study was to measure the morphometry of proximal femur and the secondary objective was to determine the association of the morphometric parameters of proximal femur with gender and body mass index (BMI). patients with unilateral hip fracture presenting to the Department of Orthopedics between 1st Jan 2017 to 30th June 2017.…”
mentioning
confidence: 99%